BUILDING A SYNERGY BETWEEN THE HALAL INDUSTRY AND THE GREEN INDUSTRY IN THE MAQĀṢID AL-SHARI’AH REVIEW AS THE BASIS OF ISLAMIC ECONOMICS - Fageh, Achmad (Universitas Muhammadiyah Surakarta, 2022)
Industrial estates are usually reflected in the existence of a sure standardization. The halal industry gave birth to Halal supply chain management, starting with halal standards procurement, manufacturing, distribution, and logistics. The green industrial area was first born by prioritizing environmental sustainability: efficiency using renewable energy, environmentally friendly substitute raw materials, and waste treatment. So far, there has not been continuity seen in the Policy, the concept of Maqāṣid al-Syari’ah as the basis of Islamic economics, which prioritizes licit and suitable goods, has not been used as a foundation to synergize the goodness of each industrial area. The method used is the library research method or literature method. The author uses the library research method to get data from reading and reviewing books, scientific articles, journals, and thesis related to the author’s title. This research offers a concept of halal and environmental sustainability, which is reflected in the following industry supply chains. (1). Procurement of goods in a halal manner with environmentally friendly product raw materials criteria. (2). Manufacturing process by prioritizing the use of renewable energy. (3). Processing of waste products (gas, liquid and solid) to not damage the surrounding environment. (4). Halal Logistics and Distribution. So that what is contained in Maqāṣid al-Syari’ah can be implemented in this new concept.